Knowledge, Attitude and Practice of Testicular Self Examination among Male Undergraduate Students of University of Nigeria Enugu Campus - Ilo, Ijeoma Judith; Omeye, Oluchi Blessing; Ede, Stephen Sunday; Chijioke, Veronica; Okoh, Chisom Favour (Journal of Drug Delivery and Therapeutics, 2022)
Background: Testicular cancer (TC) is the most common cancer in males between the age of 15 and 34 years with an incidence rates for new cases rising on an average of 0.8% each year over the last 10 years. Testicular self-examination (TSE) is the recommended preventive approach to reduce testicular Cancer (TC) mortality and morbidity.Objectives: This study examines the knowledge, attitude and practice of TSE among male undergraduate students.Methods: A descriptive research design with a sample of 343 students was recruited for the study. The students were stratified based on their faculties and convenient sampling was used to select the respondents. A self-structured questionnaire was used for data collection.Result: The findings showed that more than average (57.7%) have heard about TSE, but the level of knowledge is poor, as only (35%) have good knowledge. Their attitude is poor as (83.8%) feels it is embarrassing to touch their scrotum. Due to the poor knowledge and attitude, the majority of the respondents 133 (69.43%) did not practice TSE. Of those 59 (30.7%) that practiced, only 20 (33.9%) respondents carried it out monthly as recommended. Chi-square analysis revealed a significant relationship between their knowledge of TSE and TSE practices (p = 0.006). Conclusion: This suggests that information should be provided to the public especially; young men through television, billboard, and other media on the need for regular TSE and TSE should be integrated into the secondary school curriculum.Keywords: Testicular Self-Examination, Testicular Cancer, Nurses, Undergraduate, Enugu